Breast cancer surgery in older women: outcomes of the Bridging Age Gap in Breast Cancer study. Issue 11 (2nd June 2020) - Morgan, J. L.; George, J.; Holmes, G.; Martin, C.; Reed, M. W. R.; Ward, S.; Walters, S. J.; Cheung, K. Leung; Audisio, R. A.; Wyld, L.
Abstract : Background: Breast cancer surgery in older women is variable and sometimes non‐standard owing to concerns about morbidity. Bridging the Age Gap in Breast Cancer is a prospective multicentre cohort study aiming to determine factors influencing treatment selection and outcomes from surgery for older patients with breast cancer. Methods: Women aged at least 70 years with operable breast cancer were recruited from 57 UK breast units between 2013 and 2018. Associations between patient and tumour characteristics and type of surgery in the breast and axilla were evaluated using univariable and multivariable analyses. Oncological outcomes, adverse events and quality‐of‐life (QoL) outcomes were monitored for 2 years. Results: Among 3375 women recruited, surgery was performed in 2816 patients, of whom 24 with inadequate data were excluded. Sixty‐two women had bilateral tumours, giving a total of 2854 surgical events. Median age was 76 (range 70–95) years. Breast surgery comprised mastectomy in 1138 and breast‐conserving surgery in 1716 procedures. Axillary surgery comprised axillary lymph node dissection in 575 and sentinel node biopsy in 2203; 76 had no axillary surgery. Age, frailty, dementia and co‐morbidities were predictors of mastectomy (multivariable odds ratio (OR) for age 1·06, 95 per cent c.i. 1·05 to 1·08). Age, frailty and co‐morbidity were significant predictors of no axillary surgery (OR for age 0·91, 0·87 to 0·96). The rate of adverse events was moderate (551 of 2854, 19·3 per cent), with no 30‐day mortality. Long‐term QoL and functional independence were adversely affected by surgery. Conclusion: Breast cancer surgery is safe in women aged 70 years or more, with serious adverse events being rare and no mortality. Age, ill health and frailty all influence surgical decision‐making. Surgery has a negative impact on QoL and independence, which must be considered when counselling patients about choices. Abstract : Age, ill health and frailty all influence surgical decision‐making for breast cancer. Breast cancer surgery is safe, with serious adverse events being rare and no mortality. However, surgery has a negative impact on quality of life and independence, which must be considered when counselling patients about choices. Age defines treatment Abstract : Antecedentes: La cirugía del cáncer de mama en mujeres mayores es variable y, a veces, no estandarizada debido a las reservas que origina la morbilidad quirúrgica. Bridging the Age Gap in Breast Cancer es un estudio de cohortes, prospectivo, multicéntrico cuyo objetivo fue determinar los factores que influyen en la selección del tratamiento y en los resultados de la cirugía en pacientes mayores con cáncer de mama. Métodos: Se reclutaron mujeres de > 70 años de edad con cáncer de mama operable atendidas en 56 unidades de mama del Reino Unido entre 2013‐2018. Los datos sobre las características de la paciente y del tumor se correlacionaron con el tipo de cirugía en la mama y en la axila mediante análisis univariable y multivariable. Se controlaron los resultados oncológicos, los eventos adversos y los resultados en cuanto a la calidad de vida durante 2 años. Resultados: De 3.375 mujeres reclutadas, se realizó una intervención quirúrgica en 2.816 pacientes. Hubo 62 tumores bilaterales, por lo que se analizan 2.854 procedimientos. La mediana de edad fue de 76 años (rango 70‐95). En 1.138 pacientes se realizó una mastectomía y en 1.798 cirugía conservadora de la mama. En cuanto a la cirugía de la axila, en 575 pacientes se realizó una linfadenectomía, en 2.203 una biopsia de ganglio centinela y en 76 no se realizó ningún procedimiento. Los factores predictores de mastectomía fueron la edad, la fragilidad, la demencia y las comorbilidades (riesgo relativo, RR 1, 06; i.c. del 95% 1, 05‐1, 08), mientras que para la cirugía axilar los factores predictores fueron la fragilidad y las comorbilidades (RR 0, 91; i.c. del 95% 0, 87‐0, 96). La tasa de efectos adversos fue moderada (551/2854; 19, 3%), sin mortalidad a los 30 días. La calidad de vida a largo plazo y la independencia funcional se vieron negativamente afectadas por la cirugía. Conclusión: La cirugía de cáncer de mama es segura, con escasos efectos adversos graves y sin mortalidad. La edad, las comorbilidades y la fragilidad tienen impacto en la toma de decisiones quirúrgicas. La cirugía tiene una repercusión negativa en la calidad de vida e independencia funcional, hechos que deben ser tenidos en cuenta al aconsejar a las pacientes sobre las opciones terapéuticas.